Aktualisasi UUD 1945 dalam Praksis Ketatanegaraan Indonesia Terhadap Penyelenggaraan Kekuasaan Kehakiman Mahkamah Konstitusi - Muhammad Putra Mahardika Suma; Indy Valensia Worang (Pratyaksa: Jurnal Ilmu Pendidikan, Sosial dan Humaniora, 2025)
The Constitutional Court (MK) is a tangible manifestation of constitutional reform following the amendment of the 1945 Constitution, marking a significant change in Indonesia's constitutional system, particularly in judicial power administration. The Constitutional Court reflects Indonesia's commitment to strengthening checks and balances  in a democratic, law-based constitutional structure. The MK has strategic authority as the constitutional guardian through its functions of reviewing laws against the 1945 Constitution, resolving state institutional authority disputes, settling election result disputes, dissolving political parties, and ruling on parliamentary opinions regarding alleged presidential violations. These authorities make the MK vital in maintaining constitutional supremacy and Indonesian democratic stability. However, in practice, actualising the 1945 Constitution through MK rulings faces various complex challenges, including weak implementation mechanisms at executive and legislative levels, absent sanctions for non-compliance with MK rulings, and judicial activism tendencies potentially disrupting separation of powers and trias politica principles in the constitutional system. Through normative legal approaches and qualitative analysis of MK rulings, this study reveals how the MK serves not only as constitutional interpreter but also as a key actor safeguarding democracy, protecting human rights, and upholding rule of law in Indonesia. This study recommends achieving optimal balance between judicial activism and judicial restraint, while strengthening implementation systems for Constitutional Court decisions to realise actualisation of the 1945 Constitution that is just, sustainable, and responsive to constitutional dynamics. Effective mechanisms must ensure MK decisions translate into meaningful constitutional practice while maintaining institutional boundaries within Indonesia's democratic framework.